Pengaruh Pemasaran Digital dan Promosi Penjualan terhadap Keputusan Pembelian Konsumen pada Produk IQOS di Indonesia - Gozi, Ahmad; Zagladi, Arief Noviarakhman (IPM2KPE, 2025)
This study aims to analyze the influence of digital marketing and sales promotion on consumer purchasing decisions for IQOS products in Indonesia. The research method used is quantitative with a multiple linear regression approach. Data were collected through questionnaires distributed to 100 respondents selected using purposive sampling techniques. The results of the validity test showed that all questionnaire items were valid. Regression analysis showed that digital marketing had a positive and significant effect on purchasing decisions with a regression coefficient of 0.65 (p <0.05), while sales promotion also had a positive and significant effect with a coefficient of 0.45 (p <0.05). The R² value of 0.63 indicates that 63% of the variability in purchasing decisions can be explained by the two independent variables. These findings indicate that digital marketing has a greater influence than sales promotion in increasing consumer purchasing decisions. Effective digital marketing strategies through social media, online advertising, and the use of big data are key factors in building brand awareness and increasing consumer engagement. Meanwhile, sales promotion plays a more short-term role as a stimulus to attract the attention of new consumers. Therefore, companies are advised to optimize digital marketing to increase customer loyalty and encourage repeat purchases. Keywords: Purchase Decision, Digital Marketing, Sales Promotion